Dietary approaches in dermatological disorders: mechanisms and clinical relevance - Boluk, Patrycja; Skonieczna-Żydecka, Karolina; Zawodny, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2026)
The aim of this review was to summarise current scientific evidence on the impact of nutrition on skin condition and common dermatological diseases. An electronic literature search was conducted in PubMed and Scopus for articles published between 2008 and 2025 using relevant keywords including nutrition, skin disorders, acne vulgaris, rosacea, psoriasis, atopic dermatitis, and urticaria. Meta-analyses, randomised controlled trials, cohort studies, case-control studies, relevant animal studies, and narrative reviews evaluating dietary patterns and specific nutrients’ contribution to skin diseases were included. Essential information on study design, population characteristics, dietary interventions, and dermatological outcomes was systematically extracted and summarised. Evidence suggests that selected dietary components and specific dietary patterns may positively influence skin condition and alleviate symptoms in patients with dermatological diseases.